2016
DOI: 10.1167/iovs.15-18690
|View full text |Cite
|
Sign up to set email alerts
|

A Robust and Reliable Test to Measure Stereopsis in the Clinic

Abstract: The application enables measurements over the wide disparity range and not just at the finest disparities. In addition, it allows changes in stereopsis of the order of 1.9 to be statistically distinguished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…A staircase method was employed to determine stereoacuity threshold (arc sec). The logarithmic stereoacuity value at 50% correct was used to extrapolate the linear stereoacuity threshold reported in seconds of arc . Figure provides an example staircase and frequency of seeing curve.…”
Section: Methodsmentioning
confidence: 99%
“…A staircase method was employed to determine stereoacuity threshold (arc sec). The logarithmic stereoacuity value at 50% correct was used to extrapolate the linear stereoacuity threshold reported in seconds of arc . Figure provides an example staircase and frequency of seeing curve.…”
Section: Methodsmentioning
confidence: 99%
“…One key finding was that as many as 30% of people with otherwise normal vision were over 10 times worse than their fellows. While this might be surprising to clinicians because the present clinical tests do not reflect this 2 , it is not surprising to vision scientists, as there have been a number of laboratory studies that have suggested this 1, 39 . Although the reason for this stereo deficiency is presently unclear, Richards 4, 5 originally suggested that it may reflect a loss of a subset of disparity-sensitive neurons that process just crossed or just uncrossed disparities.…”
mentioning
confidence: 72%
“…Recently, we developed a convenient method 1 for measuring stereopsis for the clinic using an iPod, which involves depth discrimination of clouds of random dots; the subject was presented with two circular stimuli in depth side-by-side, one was in front of the screen (crossed disparity), the other was behind the screen (uncrossed disparity); the subject was asked to detect which of the two stimuli was behind the screen (i.e., a depth sign judgement). Disparity as varied using a staircase procedure until a threshold was reached.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At near, for example, the dominant quasi‐emmetropic eye without the small‐aperture device has a retinal image with higher illuminance but greater blur, so that visual acuity in that eye is markedly reduced. Stereopsis is relatively robust against modest differences in retinal illuminance but is degraded by reduced monocular visual acuity of this type …”
Section: Discussionmentioning
confidence: 99%